2016
DOI: 10.1073/pnas.1615144113
|View full text |Cite
|
Sign up to set email alerts
|

Optimal stomatal behavior with competition for water and risk of hydraulic impairment

Abstract: For over 40 y the dominant theory of stomatal behavior has been that plants should open stomates until the carbon gained by an infinitesimal additional opening balances the additional water lost times a water price that is constant at least over short periods. This theory has persisted because of its remarkable success in explaining strongly supported simple empirical models of stomatal conductance, even though we have also known for over 40 y that the theory is not consistent with competition among plants for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
328
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(338 citation statements)
references
References 92 publications
(140 reference statements)
9
328
1
Order By: Relevance
“…It is hard to understand how selection for efficient water use can operate at the level of the individual plant, because water conservation inevitably provides more water for competitors (Cowan, 2002). The alternative, protective role provides a much more convincing selective advantage to plants and seems likely to underpin the evolution of stomatal responses in the light (Wolf et al, 2016). However, as mentioned above, several lines of evidence suggest that this action may not be an ancestral character in stomatal evolution, including the widespread capacity for desiccation tolerance (Peñuelas and Munné-Bosch, 2010) in bryophytes and the fact that ancestral stomata probably aided rather than inhibited desiccation (of sporangia) in basal land plants .…”
Section: Stomata On the Primary Photosynthetic Organ And The Maintenamentioning
confidence: 99%
“…It is hard to understand how selection for efficient water use can operate at the level of the individual plant, because water conservation inevitably provides more water for competitors (Cowan, 2002). The alternative, protective role provides a much more convincing selective advantage to plants and seems likely to underpin the evolution of stomatal responses in the light (Wolf et al, 2016). However, as mentioned above, several lines of evidence suggest that this action may not be an ancestral character in stomatal evolution, including the widespread capacity for desiccation tolerance (Peñuelas and Munné-Bosch, 2010) in bryophytes and the fact that ancestral stomata probably aided rather than inhibited desiccation (of sporangia) in basal land plants .…”
Section: Stomata On the Primary Photosynthetic Organ And The Maintenamentioning
confidence: 99%
“…For example, Lu et al (2016) explored how m w should vary during multiple successive random droughts and predicted a roughly exponential decline in l over time during drought and a sigmoidal relationship between stomatal conductance and soil moisture, with closure accelerating at low soil water contents. Wolf et al (2016) took a different approach that avoided CF's arbitrary time interval and thereby obviated the Lagrange multiplier. They suggested that plants maximize "net" carbon gain-net CO 2 assimilation rate minus the carbon costs, Q, caused by low leaf xylem water potential-with respect to stomatal conductance; in other words, ∂(A -Q)/∂g s = 0.…”
Section: The Co 2 Response Problemmentioning
confidence: 99%
“…They suggested that plants maximize "net" carbon gain-net CO 2 assimilation rate minus the carbon costs, Q, caused by low leaf xylem water potential-with respect to stomatal conductance; in other words, ∂(A -Q)/∂g s = 0. Wolf et al (2016) did not explicitly identify the costs in Q but suggested they would include embolism repair and suppression of photosynthetic capacity by low water potential. They showed that maximizing A -Q was an evolutionary stable strategy under competition for water, provided the soil water potential experienced by an individual plant is insensitive to changes in that plant's transpiration rate.…”
Section: The Co 2 Response Problemmentioning
confidence: 99%
See 2 more Smart Citations